Pengembangan Media Komik Matematika pada Materi Aljabar Kelas VII - Akbar; Fitriani Nur; Muhammad Rusydi Rasyid; Munawarah; Ilhamsyah (Department of Mathematics Education, 2022)
This study aims to develop mathematical comic media on algebra material class VII SMP Negeri 1 Pitumpanua and to determine the level of validity, practicality and effectiveness of mathematical comic media in class VII algebra material of SMP Negeri 1 Pitumpanua. The type of research used is research and development with reference to the ADDIE development model which consists of 5 stages, namely analysis, design, developmet, implementation, and evaluation. The test subjects in this study were class VII SMPN 1 Pitumpanua. The instruments used in this study were expert validation sheets, observation sheets on the implementation of teaching materials, student response questionnaires, student activity observation sheets, and learning outcomes tests. The data obtained are analyzed descriptively. The results showed that comic media was in a very valid category with validation results of 4.4 meeting practical criteria based on the percentage of student response questionnaires for the overall aspect of 93% and effective based on the percentage of completeness of 87%.